So you want to design aircraft manufacturing with composites - Broge, Jean L. (United States SAE International, 2018)
Commercial aircraft are complex, sophisticated engineering marvels. And while introducing composites into new programs has added many benefits, it has also added complexity. This book aims to help manage and mitigate that complexity. To reduce the learning curve, the book opens with a refresher of key criteria involved with the forming of aerospace components, and then moves on to take a provocative look at the real-world practicality of manufacturing composite parts to rigid, at times untestable, specifications. The book then segues into suggesting a few "rules of design" for manufacturing CFRP components to minimize or avoid common production problems, and then into more specific manufacturing tools and processes that could enable larger and more complex component geometries, while retaining specific material properties and maintaining part functionality.
Includes bibliographical references.
Electronic reproduction.
Keywords: Composite materials; Airplanes -- Materials; Electronic books